Influence of fish-collagen concentrations on physicochemical properties of PVA-based hydrogel potentially for wound dressing - Muhammad Saupi, Azuri; Forid, Md. Shaekh; Cheong, Wei Teng; Wan Maznah, Wan Ishak (Elsevier Ltd, 2026)
This study aims to explore the impact of collagen concentrations on the physicochemical properties of collagen/PVA hydrogel, a widely used drug delivery carrier in biomedical and pharmaceutical research for wound dressing application. Collagen concentrations ranging from 1.5 % to 3.0 % were used to formulate collagen/PVA hydrogels with a fixed 2.0 % (w/v) PVA for each formulation. The physicochemical properties of swelling behaviour, water vapour transmission rate (WVTR), porosity, tensile strength and elongation at break that reflect to mechanical properties were measured. FTIR and SEM were used to characterize the functional groups and morphology of the hydrogels, respectively. Collagen/PVA hydrogels with 1.5 % - 2.5 % collagen concentrations showed swelling rates of 403–449 %, with the lowest swelling rate of 395 % at 3.0 %. The lowest WVTR was found in 1.5 % hydrogels, while the highest was in 3.0 % hydrogels. Lower WVTR indicates better hydrogel moisture and air retention. However, higher collagen concentrations decreased hydrogel porosity and tensile strength. 1.5–2.0 % hydrogels were more porous, elastic, and had higher mechanical strength. FTIR spectroscopy revealed functional peaks in single collagen and PVA in all hydrogels. SEM revealed a regular, round-shaped pore morphology similar to collagen pores. Collagen/PVA hydrogels at 1.5 % and 2.0 % could be appropriate for use in the fabrication of hydrogels such as for wound dressing applications.